2018
DOI: 10.1093/nar/gky1122
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of cosolutes and crowding on the volumetric and kinetic profile of the conformational dynamics of a poly dA loop DNA hairpin: a single-molecule FRET study

Abstract: We investigated the volumetric and kinetic profile of the conformational landscape of a poly dA loop DNA hairpin (Hp) in the presence of salts, osmolytes and crowding media, mimicking the intracellular milieu, using single-molecule FRET methodology. Pressure modulation was applied to explore the volumetric and hydrational characteristics of the free-energy landscape of the DNA Hp, but also because pressure is a stress factor many organisms have to cope with, e.g. in the deep sea where pressures even up to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 76 publications
3
44
0
Order By: Relevance
“…Henceforth, knowledge about high hydrostatic pressure (HHP) effects on biological systems is fundamental for our understanding of life in the deep sea, which is also thought to be the potential birth place of life on Earth, and for the search for life on extraterrestrial planets and moons 19 . HHP can affect a variety of biomolecular structures, including membranes, proteins, and non-canonical nucleic acid structures [13][14][15][20][21][22][23][24][25] . Depending on the biological system, to induce significant structural and functional changes, pressures ranging from hundreds to thousands bar must be applied.…”
mentioning
confidence: 99%
“…Henceforth, knowledge about high hydrostatic pressure (HHP) effects on biological systems is fundamental for our understanding of life in the deep sea, which is also thought to be the potential birth place of life on Earth, and for the search for life on extraterrestrial planets and moons 19 . HHP can affect a variety of biomolecular structures, including membranes, proteins, and non-canonical nucleic acid structures [13][14][15][20][21][22][23][24][25] . Depending on the biological system, to induce significant structural and functional changes, pressures ranging from hundreds to thousands bar must be applied.…”
mentioning
confidence: 99%
“…At ambient temperature and pressure conditions, the ratio of the open to closed state is approximately 0.81. [33] As shown in Figure 1B,w ith increasing a-Syn concentration af urther broad peak centered at E values around 0.5 to 0.6 emerges in the FRET histograms, which points to ap opulation of intermediate states of theD NA-HP induced by non-specific interactions with the monomeric a-Syn. The fractions of open, intermediate and closed conformations can be determined from the respective area under the curve for each distribution ( Figure 1C).…”
mentioning
confidence: 75%
“…Recently,i th as been shown that HHP application on the DNA-HP in neat buffer solution gradually populates the low-FRET distribution species( E % 0.3), which is due to the unfolding of the DNA-HP. [25,32,33] Figures 1D and Figure 2d isplay the pressuree ffecto nt he conformational states of the DNA-HP in the presence of different concentrations of a-Syn (the smFRET histograms are shown in Figure S1). From these and literature data for the DNA-HPs ystem in neat buffer solution (Figures 3 and 4i nR ef.…”
mentioning
confidence: 99%
“…24,[32][33][34][35][36][37][38] Moreover, pressure-axis experiments have also been carried out to explore the conformational landscape of DNA hairpins, Gquadruplexes and i-motifs, and it has been found that, different from the rather pressure-stable B-DNA, that noncanonical DNA and RNA structures are more susceptible to pressure modulation. 18,24,[39][40][41][42][43][44] To gain a better molecular-level and mechanistic understanding of the interaction of a-Syn in its monomeric and aggregated state with such noncanonical chromosomal DNA sequences, we carried out conformation-sensitive singlemolecule Förster resonance energy transfer (sm-FRET) experiments in concert with the pressure perturbation approach. Pressure-dependent confocal sm-FRET experiments to explore folding reactions and conformational transitions of nucleic acids have been successfully introduced, recently.…”
mentioning
confidence: 99%
“…Pressure-dependent confocal sm-FRET experiments to explore folding reactions and conformational transitions of nucleic acids have been successfully introduced, recently. [42][43][44] This method avoids ensemble averaging, which enables us to elucidate the conformational dynamics of the noncanonical DNA structures and how they are affected by the interaction with monomeric and aggregated a-Syn also in a pressure-dependent manner, allowing us to extract volumetric changes accompanying the structural conversions. As paradigmatic examples, we utilized a DNA hairpin (DNA Hp) and a telomeric i-motif (hTel i-motif) of sequence (CCCAAT) 3 CCC with a double-strand part for the second FRET label (for details, see the ESI †).…”
mentioning
confidence: 99%